Multilayered current-induced domain wall motion in Pt/Tb-Co/Ta/Tb-Co/Pt magnetic wire - Yuichiro Kurokawa; Hiroyuki Awano (AIP Advances, 2018)
We fabricated a Pt (3 nm)/Tb0.28Co0.72 (4 nm)/Ta (4 nm)/Tb0.26Co0.74 (4 nm)/Pt (3 nm) multilayered magnetic wire and investigated current-induced domain wall motion within it. We found that the Hall resistance of the Pt/Tb-Co/Ta/Tb-Co/Pt wire has four stable levels under a magnetic field of zero. Moreover, we observed that the domain walls in both the upper and lower ferromagnetic layers are controlled by a single current source. This indicates that Pt/Tb-Co/Ta/Tb-Co/Pt wire can be used in multi-level magnetic wire memory.